Birth Rituals and Cultural Memory of Albanian Diaspora in Ukraine - DUGUSHINA, Aleksandra (Poznańskie Studia Slawistyczne, 2019)
The article is devoted to the traditional birth rituals of Albanians of Ukraine reflected in their cultural memory. Several migrations from the South Albania since XV-XVI century, following by different geographic, political, ethnic and sociocultural surroundings influenced a lot Albanian traditional culture but ritual practices related to the human birth, still take a special place in the cultural memory of the Albanian diaspora. Memory on ritual practices related to the birth is mostly based on contrasting the past and present that illustrated by rituals related to the folk obstetrics and beliefs about protection, health and well-being of a mother and a child. Specificity of birth rituals is interpreted by bearers of tradition as representation of the group’s identity in a multiethnic environment in the South Ukraine and as a way for Albanians to save and transmit their culture.